The Role of Omega-3 Fatty Acids in Cognitive Health: From Development to Aging and Neurodegenerative Protection - Adamiuk, Julia; Kopeć, Karolina; Bartoszek, Aleksandra; Marut, Agnieszka; Biskup, Marta; Misiuk, Jagoda; Skuba, Adriana; Załuska, Katarzyna; Świdniak, Agnieszka; Nykiel, Sylwia (Quality in Sport, 2025)
Introduction and Purpose Omega-3 polyunsaturated fatty acids (PUFAs), particularly docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), are essential for brain structure and function across all life stages. DHA supports synaptic plasticity, neurogenesis, and neurotransmission, while EPA modulates inflammation and cerebral blood flow. This review evaluates the impact of Omega-3 PUFAs on cognitive development, maintenance, and neuroprotection, synthesizing findings from clinical trials, observational studies, and meta-analyses. Materials and Methods A systematic review of randomized controlled trials, cohort studies, and meta-analyses was conducted. Studies on maternal Omega-3 intake and infant cognition, adult supplementation and cognitive function, and Omega-3s in aging and neurodegeneration were included. Biomarkers such as plasma DHA/EPA levels, cognitive function tests, and neuroimaging data were analyzed. Safety and tolerability were also assessed. Results Maternal DHA intake supports infant cognitive development, particularly in problem-solving and language skills, though findings vary. In adulthood, Omega-3s contribute to memory, executive function, and mood regulation, but evidence remains mixed. Higher intake is linked to slower cognitive decline and lower dementia risk, primarily via neuroinflammation reduction. Omega-3s show promise in early cognitive decline by reducing oxidative stress and β-amyloid accumulation, but their role in advanced Alzheimer’s remains unclear. Supplementation is safe, with minor side effects at high doses. Conclusion Omega-3s support cognitive function and neuroprotection, particularly in early-life development and aging. Their strongest role is in reducing neuroinflammation and slowing cognitive decline. However, benefits in healthy adults and late-stage dementia remain inconclusive. Future research should explore personalized nutrition, optimal dosage, and genetic interactionsco